Jasa Ekosistem Lamun Bagi Kesejahteraan Manusia - Yudi Wahyudin; Tridoyo Kusumastanto; Luky Adrianto; Yusli Wardiatno (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2016)
The purpose of this study was to determine the typology, seagrass ecosystem function andservices that are useful for human well-being. This research was conducted by using literaturessurvey of some scientific documents and analyzed qualitatively and described to obtain acomprehensive overview in accordance with purposes of this research. The results of this studyshows that seagrass ecosystem provides the benefits of ecosystem services are valuable andneeded humans to meet their needs and well-being, both ecologically, socially, and economically. Those ecosystem services include the following: (i) provisioning services that one of them shownby the production of a protein source necessary for mandkind, (ii) regulating services, one of whichis shown by role of seagrass in maintaining the stability of white sand beaches from abrasion, (iii)cultural services, one one which is shown by the role of seagrass in making the surrounding areaas a place for recreation, especially recreational fishing, and (iv) supporting services, one of whichis shown by the role of seagrass in the process of supplying oxygen and nutrient cycling in thewaters of the needs of fish and biota surrounding. All the ecosystem services provided to be asource of life and livelihood are needed to meet the people’s welfare. Keywords : seagrass, ecosystem services, provisioning services, regulating services,cultural services, supporting services